CD antigens 1993: an updated nomenclature for clusters of differentiation on human cells (1994)
The 5th International Workshop on Human Leukocyte Differentiation Antigens (Boston, USA, 3-7 November 1993) recommended the adoption of 48 new CD clusters and subclusters and the redefinition of 14 previously established clusters. The additions and changes made to the existing CD nomenclature are summarized in a Table.